STUDI KOMPARASI KONSEP INSAN KAMIL DAN MANUSIA PONTIFIKAL PEMIKIRAN SEYYED HOSSEIN NASR - Abdulloh Hadziq; Alfin Nor Hasan; Zulkipli Lessy (Halaqah: Journal of Multidisciplinary Islamic Studies, 2024)
This research discusses a comparative study of the concept of Insan Kamil and Seyyed Hossein Nasr's Pontifical Man.  Insan Kamil can simply be interpreted as a perfect human being. Insan Kamil is a concept first coined by Ibn Arabi and developed by Abdul Karim al-Jili, which was then developed by many subsequent scholars. Meanwhile, Seyyed's Pontifical Man is the concept of human nature and how he should act. Pontifical Man in terminology can be interpreted as a papal man, namely the link between earth and heaven. This research is library research. The results of this study indicate that the concept of Pontifical Man thought by Seyyed Hossein Nasr is a modification and codification of the concept of Insan Kamil because Pontifical Man departs from traditional traditions and genealogy of all religions.